(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2025)
Within Uruguay’s fruit plantations, both Anastrepha fraterculus Wiedemann and Ceratitis capitata Wiedemann are reported as species of economic importance. These species are polyphagous and cause economic problems in fruit orchards. Currently, different control methods and techniques are combined, but in some cases, they are insufficient to prevent the damage caused by these species. We evaluated the attractiveness of different baits for fruit flies, as well as their selectivity toward non-target arthropods, in two peach and mandarin farms in southern Uruguay. Four treatments with three replicates were evaluated: diammonium phosphate (DAP), torula yeast (PBX®), torula yeast ’type B’ and Cera Trap®/Plustrap®. Captured arthropods were separated into three groups: tephritids, beneficial and other. Tephritids were sexed, dissecting females to determine the presence of developed ovaries. All treatments were effective in capturing young females of C. capitata, while captures of A. fraterculus were very low. Captures of beneficial arthropods were relatively low, with DAP capturing the highest number. Lastly, torula yeast ’type B’ was the one that captured the greatest number of non-target insects.